Pengaruh Dukungan Sosial terhadap Work Family Conflict pada Single Mother di Kota Bandung - Bianca Clarissa Audy Putri; Anna Rozana (Bandung Conference Series: Psychology Science, 2024)
Abstract. Work family conflict is a conflict between roles in which the role pressures from the work and family domains conflict in several ways Greenhaus and Beutell (1985). Social support is a reciprocal relationship involving at least two people in terms of resources, with the aim of helping the person receiving support (House, 1983). Cohen and Wills (1985) said social support can reduce stress by changing coping patterns by influencing self-perception and individual behavior when solving problems. Factors that can reduce stress in single mothers is social support. The purpose of this study was to determine how much influence social support has on work-family conflict in single mothers. This research is a quantitative research using causality method. The population in this study were single mothers in Bandung, so it used purposive sampling with a total of 105 people. The analysis technique used is multiple linear regression. The measuring instrument used within this research are the work-family conflict scale created by Carlson & Kacmar which has been translated to Indonesian by Kuntari (2014) and the social support measurement developed by Parasuraman based on House (1983) and has been adapted by researchers. The results showed that social support had a significant negative effect on work-family conflict in single mothers in Bandung by 9.8%. The biggest influence is the support of colleagues at 7.82%. Abstrak. Work family conflict merupakan konflik antar peran di mana tekanan peran dari domain pekerjaan dan keluarga saling bertentangan dalam beberapa hal Greenhaus dan Beutell (1985). Dukungan sosial adalah hubungan timbal balik yang melibatkan sekurangnya dua orang dalam hal sumber daya, dengan tujuan membantu orang yang menerima dukungan (House, 1983). Cohen dan Wills (1985) mengatakan dukungan sosial dapat mengurangi stres dengan mengubah pola koping dengan mempengaruhi persepsi diri dan perilaku individu ketika menyelesaikan masalah. Faktor yang dapat mengurangi stres pada single mother adalah dukungan sosial. Tujuan penelitian ini adalah untuk mengetahui seberapa besar pengaruh dukungan sosial terhadap work family conflict pada single mother. Penelitian ini merupakan penelitian kuantitatif dengan menggunakan metode kausalitas. Populasi dalam penelitian ini adalah single mother di Kota Bandung sehingga menggunakan purposive sampling dengan jumlah 105 orang. Teknik analisis yang digunakan adalah uji linear berganda. Alat ukur yang digunakan adalah Work-family conflict scale dari Carlson & Kacmar yang diadaptasi oleh Kuntari (2014) dan alat ukur dukungan sosial (1983) yang dikembangkan oleh Parasuraman dan telah diadaptasi oleh peneliti. Hasil penelitian menunjukkan bahwa dukungan sosial berpengaruh negatif signifikan terhadap work family conflict pada single mother di Kota Bandung sebesar 9,8 %. Pengaruh paling besar yaitu dukungan rekan kerja sebesar 7,82%.